Localized Heating and Dynamics of the Solar Corona due to a Symbiosis of Waves and Reconnection - A. K. Srivastava; Sripan Mondal; Eric R. Priest; Sudheer K. Mishra; David I. Pontin; R.Y. Kwon; Ding Yuan; K. Murawski; Ayumi Asai (The Astrophysical Journal)
The Sun’s outer atmosphere, the corona, is maintained at mega-Kelvin temperatures and fills the heliosphere with a supersonic outflowing wind. The dissipation of magnetic waves and direct electric currents are likely to be the most significant processes for heating the corona, but a lively debate exists on their relative roles. Here, we suggest that the two are often intrinsically linked, since magnetic waves may trigger current dissipation, and impulsive reconnection can launch magnetic waves. We present a study of the first of these processes by using a 2D physics-based numerical simulation using the Adaptive Mesh Refined Versatile Advection Code. Magnetic waves such as fast magnetoacoustic waves are often observed to propagate in the large-scale corona and interact with local magnetic structures. The present numerical simulations show how the propagation of magnetic disturbances toward a null point or separator can lead to the accumulation of the electric currents. Lorentz forces can laterally push and vertically stretch the magnetic fields, forming a current sheet with a strong magnetic field gradient. The magnetic field lines then break and reconnect and so contribute toward coronal heating. Numerical results are presented that support these ideas and support the concept of a symbiosis between waves and reconnection in heating the solar corona.